الاستعانة بالحاسبات الالكترونية في تدريس مواد المحاسبة - بن غربية, سالم (Dirasat in Economics and Business, 1984)
It is recommended also that a computer center, as compared to some other fo roms of computer configuration should be choosen. One of the biggest advan tages of this type of computer is to fa cilitate and encourage empirical and scientific research which the University has the main responsibility to fulfill. The purpose of this article 'vhihpub lished in the Arabic section of this issue is towfold; First, to review related literature concerning the using of com püter assisted instructio. Second, to susscst some application of computer in the Accounting courses in our school. Some suggestions — concering the computcr applications in Accounting courses — are discussed by the article. * Assistant Professor, Departement of Accounting Faculty of Economics – University of Garyounis.